MAKNA ZIARAH MAKAM SYEKH ABDURRAHMAN SIDDIQ AL-BANJARI DI PARIT HIDAYAT DESA TELUK DALAM KECAMATAN KUALA INDRAGIRI KABUPATEN INDRAGIRI HILIR - Handayani, Sri Wahyu; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Parit Hidayat in Teluk Dalam village. The purpose of this research was to find out the pilgrimage procession to Sheikh Abdurrahman Siddiq Al-Banjari's tomb. The focus of this research is the process of tomb pilgrimage, the meaning of the tomb pilgrimage, and the intention of pilgrims makes pilgrimage to the tomb of Sheikh Abdurrahman Siddiq Al-Banjari. The researcher used the descriptive qualitative methods. The informants in this research were 6 informants. Data collection used method of observation, interviews, and documentation. Sheikh Abdurrahman Siddiq Al-Banjari is a leader of the kingdom of Indragiri. This research found that people makes pilgrimage to Sheikh Abdurrahman Siddiq's tomb every day. Sheikh Abdurrahman Siddiq's tomb was also used as an intermediary to pray for the people. The people believes that by visiting the tomb of Shaykh Abdurrahman Siddiq, all wish the people pray will be carried out, because Sheikh Abdurrahman Siddiq immediately convey the wish of the pilgrims to Allah. So as to give rise to a desire to be achieved by pilgrims when on pilgrimage to Sheikh Abdurrahman Siddiq tomb. Keywords: Tradition, Culture, Tomb Pilgrimage